Synthesis and Antimicrobial Activity of Some Novel Thiazolidine-2,4-dione Derivatives - Menteşe, Arzu; Ceylan-Ünlüsoy, Meltem; Bozdağ-Dündar, Oya; Altanlar, Nurten; Ertan, Rahmiye (Arzneimittelforschung, 2009)
In this study, a series of phenylefhylsul-fanyl-1,3-thiazolo-thiazolidine-2,4-dione derivatives (VII a –f, VIII a–f) and 5-methyl-[1,2,4] triazolyl-sulfanyl-1,3-fhia-zolo-thiazolidine-2,4-dione derivatives (IXa–f, Xa–f) were synthesized and evaluated for their antibacterial and antifungal activities against S. aureus (ATCC 25923), methicillin resistant S. aureus (MRSA ATCC 43300), B. subtilis (ATCC 6633), E. coli (ATCC 23556) and C. albicans (ATCC10145). All the compounds were found active against used bacteria.
Keywords: Antimicrobial activity; Thiazoles; Thiazolidine-2,4-diones; Triazoles